Lipid Profile of Children with Malaria by Plasmodium vivax. (5th December 2016) - Dias, Rosa Maria; Vieira, Jose Luiz Fernandes; Cabral, Bianca da Conceição; da Silva, Isameriliam Rosaulem Pereira; Brasil, Laelia Maria Barra Feio; Araújo, Eliete da Cunha; de Andrade, Marcieni Ataíde
Abstract : Background . Changes in lipid profile are commonly reported in adult patients with malaria. However, a few studies evaluated lipid abnormalities in children continuously exposed to P. vivax . Objective . To evaluate lipid abnormalities in children with P. vivax infection and to assess if parasite count or the history of malaria correlates with lipid levels at admission. Methods . A total of 75 children were included in the study, from which 43 were slide confirmed infection by P. vivax . Serial blood samples were collected at admission and, on days 7 and 14, evaluated for the colorimetric measurements of triglycerides, very low-density lipoprotein (VLDL), total cholesterol, high-density lipoprotein (HDL), and low-density lipoprotein (LDL). Results . The levels of total cholesterol, LDL, and HDL were significantly lower in malaria cases. The levels of VLDL and triglycerides were significantly higher in children with malaria. Such changes were transient and were not associated with parasite counting as well as with the history of malaria of patients. Conclusion . There are significant lipid abnormalities in children with low level of P. vivax infection and mild signs and symptoms of the disease, which are not associated with parasitaemia and previous episodes of disease.